ACTIVITIY-BASED MANAGEMENT IN A REENGINEERING ENVIRONMENT - Lima, Paulo Corrêa; Di Domenico, Gino Berninzon (Anais do Congresso Brasileiro de Custos - ABC)
Process Reengineering and Activity-Based Cost have demonstrated in many companies to be working methods that guide them to excellence status. Thus, this work shows the main concepts of Reengineering and Activity Based Cost on a restructuring enterprise basis. In this work, cost indexes (cost performance measures) are presented for the management of an organized structure (established in a reengineering process) of the agricultural industry field based on an activity based cost system. Starting from these measures and the proposed structure, some important points are analyzed, such as: compatibility between activity based costing and the proposed restructuring based on reengineering; relationship between service suppliers and internal clients. The work comes to the end analyzing some considerations about the role of cost indexes as a tool to Activity-Based Management and the variability of indexes in the agroindustry field.